A sulfur-doped copper oxide catalyst and its preparation method and application

Through the preparation and optimization process of sulfur-doped copper oxide catalyst, the problem of limited effect of copper oxide catalyst in photocatalytic degradation of antibiotics is solved, and an efficient, economical and environmentally friendly antibiotic degradation effect is achieved, especially in the degradation of sulfamethoxazole. It exhibits excellent catalytic performance and stability.

CN116510750BActive Publication Date: 2024-12-13CHONGQING UNIV OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310635161.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2024-12-13
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

Existing copper oxide catalysts have limited catalytic effects when photocatalyzing the degradation of antibiotics, and conventional treatment methods are costly and complex, so more effective photocatalytic materials are needed to solve this problem.

Method used

Through the preparation method of sulfur-doped copper oxide catalyst, the autoclave reaction was carried out and the synthesis process was optimized to prepare sulfur-doped with high specific surface area and good crystallization performance using a molar ratio of CuSO4·5H2O and Na2S2O3. Copper oxide catalyst used to activate PMS to degrade antibiotics.

Benefits of technology

The ultrafast degradation effect of sulfur-doped copper oxide catalyst in degrading the antibiotic sulfamethoxazole is achieved, with excellent catalytic performance, strong stability, and economical and environmentally friendly advantages. It is widely used in the degradation of a variety of antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116510750B_ABST
    Figure CN116510750B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a sulfur-doped copper oxide catalyst, which relates to the technical field of catalytic materials and comprises the following steps: (1) 4 ·5H 2 O was dissolved in a certain amount of deionized water, and then NaOH solution was added and magnetically stirred for 10 minutes to form a mixture solution. 4 ·5H 2 The molar ratio of O to NaOH is 1:2‑4; (2) Na 2 S 2 O 3 , continue stirring for 30-40 minutes, then transfer the obtained suspension to an autoclave, react at 80-140°C for 6 hours, and after the autoclave is naturally cooled, the sample is alternately centrifuged with distilled water and ethanol for 3 times, and then dried at 60°C for 12 hours to obtain the product. The prepared sulfur-doped copper oxide catalyst activates PMS to degrade the antibiotic sulfamethoxazole, with excellent catalytic effect, strong stability, and economic and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a sulfur-doped copper oxide catalyst and a preparation method and application thereof. Background Art

[0002] Copper oxide is a typical narrowband (1.2-1.5 eV) P-type semiconductor material with a monoclinic crystal structure and lattice constants a = 0.4684 nm, b = 0.3423 nm, c = 0.5129 nm. On the CuO (110) crystal plane, copper atoms are surrounded by rectangles composed of oxygen atoms, and oxygen atoms are also surrounded by deformed copper tetrahedrons. Nano copper oxide powder has the characteristics of surface effect, quantum size effect, volume effect and macro quantum tunneling effect. Therefore, in terms of catalysis, nano copper oxide can well catalyze the degradation of residual organic dyes and antibiotics in wastewater.

[0003] The main types of commonly used antibiotics include β-lactams, macrolides, tetracyclines, quinolones and sulfonamides. These antibiotic residues are extremely harmful to human health and the environment. Conventional treatment methods such as chemical oxidation, biodegradation, membrane separation, etc. are relatively costly and complex. Photocatalytic degradation of antibiotics is a more thorough, green and safe method. Therefore, the development of more effective photocatalytic materials is of great significance.

[0004] However, the oxidation reaction between the photogenerated carriers of a single CuO nanomaterial and the target degradation product mainly depends on its intrinsic migration to the catalyst surface. The photogenerated electrons and holes are prone to positive and negative attraction during the migration process, and the catalytic effect is limited. In order to obtain more superior photocatalytic performance, the current research on copper oxide is mainly focused on the modification of copper oxide, such as optimizing the morphology of copper oxide, doping modification, surface modification or constructing heterojunctions, etc. However, what elements to use for doping, whether the catalytic performance can be improved after doping, and how to optimize the synthesis process to further improve and expand its application in catalytic degradation are problems that technicians in this field need to solve. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a sulfur-doped copper oxide catalyst to address the deficiencies of the prior art. The sulfur-doped copper oxide catalyst prepared by S doping and preparation process optimization can activate PMS to degrade the antibiotic sulfamethoxazole, has excellent catalytic effect, can achieve ultrafast degradation, has strong stability, and is economical and environmentally friendly.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a sulfur-doped copper oxide catalyst comprises the following steps:

[0008] (1) CuSO4 ·5H 2 O was dissolved in a certain amount of deionized water, and then NaOH solution was added and magnetically stirred for 10 minutes to form a mixture solution. 4 ·5H 2 The molar ratio of O to NaOH is 1:2-4;

[0009] (2) Add Na to the mixture solution 2 S 2 O 3 , continue stirring for 30-40 minutes, then transfer the obtained suspension into an autoclave, react at 80-140°C for 6 hours, after the autoclave is naturally cooled, the sample is alternately centrifuged with distilled water and ethanol for 3 times, and then dried at 60°C for 12 hours to obtain the product;

[0010] The CuSO 4 ·5H 2 O and Na 2 S 2 O 3 The molar ratio is 1:0.25-1.

[0011] Furthermore, the reaction temperature in step (2) is 100°C.

[0012] Furthermore, the CuSO 4 ·5H 2 O and Na 2 S 2 O 3 The molar ratio is 1:0.5.

[0013] A sulfur-doped copper oxide catalyst, wherein the O on the catalyst surface comprises adsorbed oxygen O-1, advanced oxide species O-2 and lattice oxygen O-3, wherein the content of the adsorbed oxygen O-1 is 14.96%, the content of the advanced oxide species O-2 is 18.97%, and the content of the lattice oxygen O-3 is 66.07%.

[0014] Application of a sulfur-doped copper oxide catalyst in activating PMS to degrade antibiotics.

[0015] Furthermore, the reaction conditions for the degradation of the antibiotic sulfamethoxazole were as follows: the initial concentration of the antibiotic was 20 mg·L -1 The catalyst dosage is 0.05-0.2g·L -1 , PMS dosage is 0.01-0.5mM, pH=5-7.

[0016] Furthermore, the reaction conditions for the degradation of the antibiotic sulfamethoxazole were as follows: the initial concentration of the antibiotic was 20 mg·L -1 The catalyst dosage is 0.1 g·L -1, PMS dosage is 0.5mM, pH=6.4.

[0017] The beneficial effects of the present invention are:

[0018] 1. The present application discloses a sulfur-doped copper oxide catalyst, in which sulfur is doped into copper oxide, and the doped S is uniformly distributed in the CuO crystal structure, which greatly improves the efficiency of the catalyst in activating PMS to degrade antibiotics. Specifically, the following points are made: (1) The catalyst has a uniform nanosheet structure with a pore size of 28.49 nm and a large specific surface area; (2) After sulfur doping, the proportion of lattice oxygen on the catalyst surface changes greatly, and the oxygen on the catalyst surface includes adsorbed oxygen O-1, advanced oxide species O-2, and lattice oxygen O-3. The content of the adsorbed oxygen O-1 is 14.96%, and the content of the advanced oxide species O-2 is 1 8.97%, and the content of lattice oxygen O-3 is 66.07%, that is, the proportion of lattice oxygen on the catalyst surface increased by 30.4% after sulfur doping, and the proportion of adsorbed oxygen decreased by 11.18%, resulting in point defects and crystal shearing, which greatly promoted the catalytic reaction; (3) S doping enhances the bonding ability of Cu atoms and O atoms, and also improves the covalency of Cu-O bonds; and the higher overlap of Cu2p, S2p and O1s orbitals further indicates the formation of Cu-SO bonds. The enhancement of bonding ability, covalency and the formation of Cu-SO promote electron transfer, further improving the catalytic activity of PMS activation. (4) After forming an interface with PMS, the electron transfer between S-CuO and PMS is more obvious, that is, the electron transfer from the doped catalyst to PMS is easier.

[0019] 2. This application successfully doped S into CuO by optimizing the raw materials and synthesis temperature, and prepared a catalyst with large specific surface area, high purity and good crystallization performance. The preparation process is simple, does not require the addition of additional guiding agents, dispersants and solvents, and has more economic and environmental benefits.

[0020] 3. In this application, the S doping amount has a great influence on the catalytic efficiency. When Cu / S is 1:1, the charge transfer resistance at the interface between the catalyst and the electrolyte solution is the smallest, the size of the catalyst is the smallest, and the degradation efficiency of antibiotics is the highest.

[0021] It was applied to activate PMS to degrade the antibiotic sulfamethoxazole, and the initial concentration of the antibiotic sulfamethoxazole was controlled to be 20 mg·L -1 The catalyst dosage is 0.1 g·L -1 , PMS dosage is 0.5mM, pH=6.4, sulfamethoxazole can be completely degraded in 1min, and the reaction kinetics is 0.462s -1 , can achieve ultrafast degradation, and has excellent catalytic performance. Moreover, the catalyst of the present application also has excellent degradation performance for enrofloxacin, sulfapyridine, and sulfachloropyridazine, and has a wide range of applications.

[0022] 4. In the five repeated operations, the degradation efficiency of sulfamethoxazole was still very high and the structural stability was strong; and the introduction of S greatly inhibited the leaching of Cu and reduced secondary pollution.

[0023] Moreover, the transformation products of sulfamethoxazole in the 1-S-CuO / PMS system are simpler, less toxic, economical and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD patterns of CuO and 1-S-CuO;

[0025] Figure 2 SEM images (a) and (b), HRTEM image (c), HAADF (d) and EDX (d) spectra of 1-S-CuO;

[0026] Figure 3 N of CuO (a) and 1-S-CuO (b) 2 Adsorption-desorption isotherms and pore size distribution curves;

[0027] Figure 4 FTIR spectra of CuO and 1-S-CuO;

[0028] Figure 5 XPS measurement spectra of CuO and 1-S-CuO samples (a), S2p (b), O1s (c), Cu2p (d);

[0029] Figure 6 (a) Degradation of sulfamethoxazole in different reaction systems, (b) Degradation efficiency of various antibiotics by 1-S-CuO / PMS catalytic system;

[0030] Figure 7 (b) The effect of the degree of sulfidation on the degradation of SMX and the electrochemical impedance spectra at different degrees of sulfidation;

[0031] Figure 8 SEM images of 2-S-CuO (a, d), 0.6-S-CuO (b, e) and 0.5-S-CuO (c, f);

[0032] Fig. 9 The effect of catalyst dosage (a), PMS dosage (b), synthesis temperature (c), and initial pH (d) on SMX degradation.

[0033] Fig.10 SEM images of 1-S-CuO synthesized at different hydrothermal reaction temperatures, 80℃(a), 120℃(b), 140℃(c), 160℃(d);

[0034] Fig.11 This is the five consecutive degradation diagrams of sulfamethoxazole in 1-S-CuO system;

[0035] Fig.12 XPS measurement spectra of 1-S-CuO before and after use (a), S2p (b), O1s (c), Cu2p (d);

[0036] Fig.13 The chemical structures of CuO(111) (a), 1-S-CuO(11) (b), CuO(-111) (c) and 1-S-CuO(-1101) (d);

[0037] Fig.14 The total density of states and the corresponding atomic partial density of states of CuO (a) and the total density of states and the atomic partial density of states of 1-S-CuO (b);

[0038] Fig.15 The adsorption structures of PMS on CuO(111) (a), 1-S-CuO(11) (b), CuO(-111) (c) and 1-S-CuO(-1101) (d); E ads and d O-O represent adsorption energy and OO bond length, respectively;

[0039] Fig.16 The structures of SMX and its transformation products on the 1-S-CuO / PMS system. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0041] The products prepared in Examples 1-4 of the present application are marked as 2-S-CuO (Cu / S is 1:2), 1-S-CuO (Cu / S is 1:1), 0.6-S-CuO (Cu / S is 1:0.6) and 0.5-S-CuO (Cu / S is 1:0.5), respectively. CuO is prepared in Comparative Example 1. SMX is the abbreviation of sulfamethoxazole, and PMS is the abbreviation of peroxymonosulfate (2KHSO 5 ·KHSO 4 ·K 2 SO 4 ).

[0042] Example 1

[0043] A method for preparing a sulfur-doped copper oxide catalyst comprises the following steps:

[0044] (1) 1 mM CuSO 4 ·5H 2CuSO was dissolved in 30 mL of deionized water, and then 2.5 mM NaOH solution (5 mL) was added to the CuSO 4 The solution was stirred magnetically for 10 minutes to form a mixture solution;

[0045] (2) Then add Na 2 S 2 O 3 , continue stirring for 30 minutes; then transfer the obtained suspension to an autoclave equipped with 100mL of polytetrafluoroethylene lining and react at 100°C for 6 hours; after the autoclave is naturally cooled, the sample is alternately centrifuged with distilled water and ethanol for 3 times, and then dried at 60°C for 12 hours to obtain the product.

[0046] In this example, 1 mM Na 2 S 2 O 3 , namely CuSO 4 ·5H 2 O and Na 2 S 2 O 3 The molar ratio was 1:1, and the product was recorded as 2-S-CuO.

[0047] Example 2

[0048] In this example, 0.5 mM Na 2 S 2 O 3 , namely CuSO 4 ·5H 2 O and Na 2 S 2 O 3 The molar ratio was 2:1, and the product was recorded as 1-S-CuO.

[0049] Example 3

[0050] In this example, 0.33 mM Na 2 S 2 O 3 , namely CuSO 4 ·5H 2 O and Na 2 S 2 O 3 The molar ratio was 3:1, and the product was recorded as 0.6-S-CuO.

[0051] Example 4

[0052] In this example, 0.25 mM Na 2 S 2 O 3 , namely CuSO 4 ·5H2 O and Na 2 S 2 O 3 The molar ratio was 4:1, and the product was recorded as 0.5-S-CuO.

[0053] Embodiment 5-8

[0054] In Examples 5-8, the reaction temperature in step (2) is changed to 80°C, 120°C, 140°C, and 160°C, respectively.

[0055] Comparative Example 1

[0056] In Comparative Example 1, no Na was added. 2 S 2 O 3 , the prepared product is CuO.

[0057] Performance Characterization

[0058] 1. XRD characterization

[0059] The phase structure of the catalyst was analyzed by X-ray diffraction, such as Figure 1 As shown. The diffraction peaks of CuO and 1-S-CuO are consistent with those of the standard card (PDF#48-1548), indicating that high-purity samples were prepared. The characteristic peaks are wide and narrow, smooth and sharp, indicating that the prepared samples have good crystallinity. The typical CuO diffraction peaks at 35.499°, 38.727° and 48.727° are attributed to the (002), (111) and (202) lattice planes of CuO, respectively. Compared with CuO, the diffraction peaks of the 1-S-CuO sample did not change significantly, indicating that S doping did not change the lattice structure of CuO.

[0060] 2. SEM and HRTEM characterization

[0061] Scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) images of 1-S-CuO are shown in Figure 2. Figure 2 shown. Figure 2 As shown in ab, 1-S-CuO is a nano-stacked sheet structure with clear edges, and the length of the stacked sheets is 50nm-1μm.

[0062] Typical HRTEM images ( Figure 2 c) shows good crystals and clear sample lattice fringes. The interplanar spacing of 0.2946nm corresponds well to the (020) plane of the 1-S-CuO monoclinic crystal structure. In addition, the EDS element mapping image ( Figure 2 d) It was confirmed that S was successfully doped into CuO and Cu, O, and the S element was uniformly distributed in the 1-S-CuO system.

[0063] 3. BET characterization

[0064] Figure 3 (a) and (b) are the N of CuO and 1-S-CuO, respectively. 2 Adsorption-desorption isotherms and pore size distribution curves, where the specific surface area of ​​1-S-CuO is 10.9287 m 2 ·g -1 , pore diameter is 28.49nm, pore volume is 0.0814cm 3 ·g -1 .

[0065] The isotherms of the samples all show H 1 In the IV isotherm model of the hysteresis loop, the pore size and the volume of the catalyst first increase and then decrease. The pore size distribution activity range of the catalyst is 0-100nm, and there is a large pore size peak at 32nm, indicating that there are many stacked pores in the catalyst. 2 The adsorption-desorption isotherms show that at P / P 0 = 0.8 There is a sudden H 2 Hysteresis loop. When P / P 0 When P / P <0.8, the adsorption and desorption rates are relatively slow and the curve changes are relatively small, which confirms that the catalyst has microporous characteristics. 0 When >0.8, the adsorption and desorption rates suddenly increased and the curves changed significantly, further indicating that the catalyst has mesoporous characteristics. Combined with the pore distribution diagram of the material, the catalyst is a micro-mesoporous material, and these abundant pores provide many catalytic fields for the degradation reaction.

[0066] 4. FTIR characterization

[0067] like Figure 4 As shown, 610cm -1 The stretching vibration at 1621 cm is attributed to the Cu-O bond, further confirming that CuO and 1-S-CuO were successfully synthesized. -1 The stretching vibration at 3421 cm is attributed to the C=C bond. -1 and 3783cm -1 The stretching vibrations at are attributed to the OH- and CO bonds, respectively. The abundant functional groups are helpful for the adsorption of organic pollutants and the activation of PMS.

[0068] 5. XPS characterization

[0069] XPS spectra of CuO and 1-S-CuO are shown in Figure 5 As shown. C1s284.8eV was used as a reference to calibrate all binding energies. Characteristic peaks of Cu2p, O1s and S2p were observed in the XPS measurement spectra of CuO and 1-S-CuO. Figure 5b shows that the 161 peaks at 163.4 and 162.02 eV in 1-S-CuO can be attributed to S2p 1 / 2 and S2p 3 / 2 orbital. In addition, S is present in the SO bond as S 2+ The bond state exists, and the corresponding binding energy is 168.78eV. O1s spectrum ( Figure 5 c) can be divided into three peaks, representing adsorbed oxygen (O-1, 529.93 eV), advanced oxide species (O-2, 531.36 eV) and lattice oxygen (O-3, 532.65 eV). After S doping, the split peak results of O1s show that the lattice oxygen ratio of O-3 on the catalyst surface increased by 30.4%, and the adsorbed oxygen ratio decreased by 11.18%, resulting in point defects and crystal shearing, which further promoted the catalytic reaction. Cu2pXPS spectrum ( Figure 5 d) is well divided into two spin orbits. The peaks with binding energies of 956.91, 938.18, and 936.58 eV can be attributed to Cu 2+ 2p 1 / 2 , Cu 2+ 2p 3 / 2 and Cu + 2p 3 / 2 orbit. The satellite peaks are at 947.48 eV and 947.78 eV, respectively. In addition, the binding energy of Cu2p in 1-S-CuO increases compared with CuO, which indicates that the electron cloud around the copper atoms is thinner due to electron loss. The results confirm the successful synthesis of S-doped CuO. Table 1 summarizes the three chemical components and their valence state distribution on the catalyst surface.

[0070] Table 1 Three chemical components and their valence distribution on the catalyst surface

[0071]

[0072] Application test

[0073] Catalytic application experiments were conducted at room temperature and under natural conditions. First, 100 mL of the prepared sulfamethoxazole solution was pipetted into a beaker, 10 mg of the catalyst was added, and the mixture was stirred on a magnetic stirrer for 30 minutes to achieve adsorption-desorption equilibrium. The initial pH of the reaction solution was about 6.4. By adding 0.1 MH 2 SO 4Or 0.1M NaOH solution to adjust the pH. Then, 1 mL of PMS solution was added to start the reaction. 1 mL of the reaction solution was extracted every 10 seconds and immediately quenched with 200 μL of ethanol. The filtrate was collected after filtration through a 0.22 μm PTFE membrane. The SMX concentration was preliminarily tested by ultra-performance liquid chromatography (UPLC). Each experiment was performed three times. After each run, the catalyst was centrifuged and washed three times alternately with methanol and deionized water to remove residues. The washed catalyst was dried at 60 ° C for 12 h and reused five times in succession. C and C 0 Represent the concentration of sulfamethoxazole at time t and the initial concentration of sulfamethoxazole, respectively. With t as the horizontal axis, ln(C 0 / C t ) is the ordinate, and the slope obtained after fitting is the apparent reaction rate constant k of the reaction system.

[0074] 1. Degradation test

[0075] The CuO, 1-S-CuO, PMS, CuO / PMS and 1-S-CuO / PMS prepared in the present application were respectively applied to the degradation test of sulfamethoxazole. The reaction conditions were as follows: the catalyst concentration was 0.1 g·L -1 , pH = 6.4, the concentration of sulfamethoxazole is 20 mg·L -1 , PMS concentration was 0.50 mM, and the light source was natural light.

[0076] In addition, the degradation efficiency of 1-S-CuO / PMS system on different antibiotics, including enrofloxacin, sulfapyridine, sulfamethoxazole, and sulfachloropyridazine, was tested, and the antibiotic concentration was 20 mg·L -1 , the catalyst concentration is 0.1 g·L -1 , PMS concentration is 0.50mM, pH=6.4.

[0077] The test results can be found in Figure 6 , the adsorption performance of the catalyst itself is not obvious and the oxidation effect of PMS itself is weak. In the CuO / PMS and 1-S-CuO / PMS systems, the removal rates of sulfamethoxazole are 76.71% and 100%, respectively. Compared with the CuO / PMS system, the degradation efficiency of sulfamethoxazole in the 1-S-CuO / PMS system is increased by 23.29%. Moreover, within 1 minute, the degradation efficiencies of the four antibiotics reached 77.2%, 66.32%, 100% and 100%, respectively, which shows that the 1-S-CuO / PMS prepared in this application has a wide range of applications in degrading a variety of antibiotics.

[0078] The above application test shows that 0.1g·L -1The 1-S-CuO activated 0.5 mM PMS and completely degraded 20 ppm of sulfamethoxazole within 1 minute, with excellent catalytic performance.

[0079] 2. Reaction system optimization test

[0080] 1) S doping dose test

[0081] In order to investigate the effect of S doping dosage on the catalytic performance of S-CuO for PMS activation and SMX degradation, as Figure 7 As shown in a, the S-CuO catalysts prepared under different copper-sulfur ratios (Examples 1-4) were applied to the S-CuO / PMS catalytic system. The catalytic effect first increased and then decreased with the increase of S doping amount, which is consistent with the results of electrochemical impedance spectroscopy (EIS) ( Figure 7 b), that is, when Cu:S is 1:1, the degradation efficiency of SMX is the highest, and the reaction kinetics is 0.462s -1 When Cu:S=1:2, the reaction kinetics of SMX is only 0.008s -1 , indicating that different S doping amounts significantly changed the degradation performance.

[0082] EIS is used to analyze the charge transfer resistance between the catalyst surface and the electrolyte interface during SMX degradation. Figure 7 As shown in (b), when the Cu / S ratio is 1:1, it has the smallest semicircle diameter. At this time, the charge transfer resistance at the interface between the catalyst and the electrolyte solution is the smallest, which is conducive to the transfer of electrons from the catalyst to the reactant.

[0083] The S doping dose also affects the morphological characteristics of S-CuO. Figure 8 It can be observed that the size of the stacked sheets decreases with the increase of S doping dose and 2-S-CuO has obvious agglomeration, which may be the reason for its poor catalytic performance.

[0084] 2) Optimization test of catalyst dosage, PMS concentration, synthesis temperature and application test pH.

[0085] like Fig. 9 As shown in a, as the catalyst dosage increases from 0.05 g·L -1 Increase to 0.20 g·L -1 The corresponding reaction kinetics are from 0.0614s -1 Increased to 0.2526s -1 , indicating that the 1-S-CuO dosage determines the number of active sites in the reaction process. The more active sites there are, the easier it is to activate PMS. Based on cost considerations, the optimal dosage is 0.1 g·L -1 .

[0086] Fig. 9b shows the degradation rate of sulfamethoxazole solution at different PMS concentrations. When the concentration of PMS increased from 0.01mM to 0.5mM, the degradation rate of SMX by 1-S-CuO increased significantly, and the kinetic constants increased from 0.0093S -1 Increased to 0.462S -1 , indicating that the increase in PMS dosage can significantly promote the degradation of SMX.

[0087] like Fig. 9 As shown in c, when the synthesis temperature is 100℃, it reaches 0.462s -1 When the synthesis temperature is 80℃, the reaction kinetics is only 0.2114s -1 , because the relatively low temperature leads to slow crystal growth. When the synthesis temperature is 140 ° C, the reaction kinetics is only 0.1889s -1 , confirming that too high a synthesis temperature is not conducive to high degradation efficiency. The morphological characteristics of the catalyst at different synthesis temperatures can be seen in the SEM images ( Fig.10 ). The study found that when the temperature reached 140°C (10c) and 160°C (10d), serious agglomeration occurred, which was not conducive to the perfect crystallization of S-CuO nanoparticles.

[0088] Since solution pH affects the distribution ratio of ionic species and the generation of free radicals, the effect of solution pH on the degradation of SMX was discussed. 2 SO 4 or 0.1 M NaOH solution to adjust the initial pH of the solutions to 3, 5, 7, and 9. After adding PMS, the pH values ​​of all solutions dropped to 4-5, and then the pH of the solutions increased slightly with the reaction time. Fig. 9 d shows that the degradation characteristics changed significantly within the initial pH range of 3 to 9. The optimal pH for SMX degradation was 6.4, and the corresponding reaction kinetics was 0.462 s -1 At pH = 5, the reaction kinetics dropped to 0.0595s -1 ; At pH = 3, the reaction rate further decreased to 0.0139s -1 The degradation reaction was almost completely inhibited. At pH = 9, the reaction kinetics was 0.0163s -1 It only exhibits excellent degradation characteristics under weakly acidic conditions. This suggests that the active surface centers of the catalyst are easily affected by H + and OH - impact.

[0089] 3) Stability and reusability

[0090] In five repeated operations, the degradation efficiency of SMX still reached 56.72% within 1 min, indicating that the synthesized catalyst exhibits good reusability ( Fig.11 ). Based on the XPS comparison, the comprehensive investigation results of the fresh catalyst and the used catalyst, the characteristic peaks of Cu, O and S of the used catalyst were detected ( Fig.12 ), the intensity of each peak changes slightly, indicating that the catalyst structure of the present application is highly stable.

[0091] In addition, the concentration of CuO / SMX / PMS system was 0.4385 mg·L after 1 min of reaction. -1 , the concentration of Cu in the 1-S-CuO / SMX / PMS system is 0.1540 mg·L -1 , it can be seen that the introduction of S can inhibit the leaching of copper ions, thereby reducing secondary pollution.

[0092] 3. Catalytic mechanism of PMS activation

[0093] from Fig.13 It can be seen that by comparing the chemical structures of the (111) and (-111) crystal planes of CuO and 1-S-CuO, it can be seen that the chemical structure of CuO does not change before and after S doping. Cu-SO bonds can be found in the structure of 1-S-CuO.

[0094] Depend on Fig.14 It can be seen that the density of states (DOS) changes significantly before and after S doping, especially on both sides of the Fermi level. The pseudogap of 1-S-CuO is wider than that of CuO. S doping not only enhances the bonding ability of Cu atoms and O atoms, but also improves the covalency of the Cu-O bond. In addition, the higher overlap of Cu2p, S2p, and O1s orbitals further indicates the formation of Cu-SO bonds. The enhancement of bonding ability, covalency, and the formation of Cu-SO promote electron transfer, which further improves the catalytic activity of PMS activation.

[0095] The optimized adsorption configurations of PMS on different crystal planes are as follows: Fig.15 As shown in the figure, the higher the absolute value of the calculated adsorption energy, the more stable the structure. The adsorption energies of PMS on CuO(111) and S-CuO(111) surfaces are -0.726 eV and -1.836 eV, respectively. The adsorption energies of CuO(-111) and S-CuO(-111) surfaces are -0.513 eV and -1.421 eV, respectively. This indicates that PMS is more easily adsorbed by 1-S-CuO. The OO bond length in free PMS is 369

[69] The OO bond lengths of PMS on the CuO(111) surface and S-CuO(112) surface are and However, the OO bond lengths of PMS on CuO(-111) and S-CuO(-111) are and

[0096] It can be concluded that, on the one hand, PMS adsorbed on the active surface can extend the O-O bond of PMS. On the other hand, S-CuO is relatively easy to break the O-O bond in PMS compared with CuO.

[0097] 4. Toxicity assessment of SMX degradation products

[0098] Fig.16 In the paper, two possible degradation pathways of sulfamethoxazole in 2-S-CuO / PMS system were proposed. In pathway I, first, -NH 3 The free radical attacks the hydroxylamine derivative of SMX, TP-1 (m / z = 270). Subsequently, the SN bond breaks under the attack of ·OH to produce TP-2 (m / z = 174). The amino group on the benzene ring of TP-3 (m / z = 156) is oxidized to a nitro group to form TP-4 (m / z = 142), which then produces the simpler TP-5 (m / z = 123). In pathway II, the -NH 2 The group is highly active and is easily oxidized by the active substances in the 2-S-CuO / PMS system to form nitro SMX (TP-6, m / z = 284). The continuous attack of hydroxyl radicals causes the benzene ring of TP-6 ​​to split and replace the carbon atom with a hydroxyl ion to form TP-7 (m / z = 246). The ON bond of TP-7 is cleaved by free radicals to form a small molecule compound TP-8 (m / z = 215), and the SN bond is cleaved to form a large molecule compound TP-10 (m / z = 203).

[0099] Table 2 Toxicological analysis of degradation intermediates using T·E·S·T software

[0100]

[0101] Toxicity evaluation of MX degradation products The potential toxicity of SMX and its transformation products for five key indicators (LC50-96hr, rat oral LD50, bioconcentration factor, developmental toxicity and mutagenicity) was evaluated using TEST software. As shown in Table 2, the oral rat LD50 of the transformation products was lower than that of SMX. In addition, except for TP-4, the bioconcentration factors of all intermediates were lower than that of SMX. In addition, except for TP-1 (0.93 toxicity), which was slightly higher than SMX (0.85 toxicity), the developmental toxicity of all transformation products was lower than that of SMX. Similarly, except for TP-7, all intermediates were considered to have "positive" mutagenicity. It shows that the transformation products of SMX in the 1-S-CuO / PMS system are simpler and less toxic.

[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a sulfur-doped copper oxide catalyst, characterized in that: The sulfur-doped copper oxide is doped with S uniformly distributed in the CuO crystal structure, comprising the following steps: (1) dissolving CuSO4·5H2O in a certain amount of deionized water, then adding NaOH solution, and magnetically stirring for 10 minutes to form a mixture solution, wherein the molar ratio of CuSO4·5H2O to NaOH is 1:2-4; (2) Na2S2O3 was added to the mixture solution, and the stirring was continued for 30-40 minutes. Then the obtained suspension was transferred to an autoclave and reacted at 80-140°C for 6 hours. After the autoclave was naturally cooled, the sample was centrifuged three times alternately with distilled water and ethanol, and then dried at 60°C for 12 hours to obtain the product; The molar ratio of CuSO4·5H2O to Na2S2O3 is 1:0.25-1.

2. The method for preparing a sulfur-doped copper oxide catalyst according to claim 1, characterized in that: The reaction temperature in step (2) is 100°C.

3. The method for preparing a sulfur-doped copper oxide catalyst according to claim 1, characterized in that: The molar ratio of CuSO4·5H2O to Na2S2O3 is 1:0.

5.

4. A sulfur-doped copper oxide catalyst prepared by the preparation method of claim 1, characterized in that: The O on the catalyst surface includes adsorbed oxygen O-1, advanced oxide species O-2 and lattice oxygen O-3, wherein the content of the adsorbed oxygen O-1 is 14.96%, the content of the advanced oxide species O-2 is 18.97%, and the content of the lattice oxygen O-3 is 66.07%.

5. Use of the sulfur-doped copper oxide catalyst prepared by the preparation method of claim 1 in activating PMS to degrade antibiotics.

6. The use according to claim 5, characterized in that: The reaction conditions for the activated PMS to degrade the antibiotic sulfamethoxazole were as follows: the initial concentration of the antibiotic was 20 mg·L -1 The catalyst dosage is 0.05-0.2g·L -1 , PMS dosage is 0.01-0.5 mM, pH=5-7.

7. The use according to claim 6, characterized in that: The reaction conditions for the activated PMS to degrade the antibiotic sulfamethoxazole are: the initial concentration of the antibiotic is 20 mg·L -1 The catalyst dosage is 0.1 g·L -1 , PMS dosage is 0.5mM, pH=6.4.